Pemberdayaan Perempuan Berkemajuan Melalui Sekolah Ibu Pintar (SEKITAR) - Dwi Yunita Haryanti; Siti Kholifah; Dina Ramadaniyah; Desta Almiira Hudoyo; Nadya Intifadha Furensa; Wasilatur Rohmah (Indonesian Journal Publisher, 2023)
Mother's knowledge is very important in carrying out her role as a mother in the family and society. An educated and knowledgeable mother can be a good role model for her family, especially children. The purpose of this community service is to prepare an informal educational platform that accompanies and teaches women, especially mothers, to become intelligent, agile and exemplary figures. This dedication partner is the Head of the Aisyiyah Branch in the Bangsalsari District. The implementation method is health education which consists of the stages of preparation, implementation and evaluation. The dedication activity was carried out on Sunday, April 16 2023 at 14.00-17.00 at the Al Furqon Mosque, Bangsalsari Village, Jember Regency which was attended by 38 participants. The result of this community service is the formation of an informal community called the Smart Mother School and its learning curriculum. The conclusion is that informal schools for mothers are one of the efforts to guard and increase the knowledge of mothers in carrying out their roles both within the family and in the community.